2017
DOI: 10.1038/srep40074
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mosquito trapping efficiency by using pulse width modulated light emitting diodes

Abstract: In this study, a light-driving bug zapper is presented for well controlling the diseases brought by insects, such as mosquitoes. In order to have the device efficient to trap the insect pests in off-grid areas, pulse width modulated light emitting diodes (PWM-LED) combined with a solar power module are proposed and implemented. With specific PWM electric signals to drive the LED, it is found that no matter what the ability of catching insects or the consumed power efficiency can be enhanced thus. It is demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…For instance, the use of high-intensity UV light during the day may not be effective in attracting nocturnal mosquitoes. Controlling the timing and light spectra may allow targeting of specific mosquito species using environmentally friendly light-based approaches [32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of high-intensity UV light during the day may not be effective in attracting nocturnal mosquitoes. Controlling the timing and light spectra may allow targeting of specific mosquito species using environmentally friendly light-based approaches [32].…”
Section: Discussionmentioning
confidence: 99%
“…UV-LTs generally collected more mosquitoes than CDC-LTs, possibly because the e cacy of incandescent light in CDC-LTs may be affected by other light sources in the night including moonlight [40]. Also, mosquitoes have diverse response to different light spectra as previously reported where mosquito response to arti cial light indicated that blue and green light is often more attractive than that in the yellow-orange and red regions of the visible spectrum [41,42]. UV-LT is a largely unexplored trapping technique that could be useful for both indoor and outdoor trapping of mosquitoes especially when evaluating outdoor deployed vector control methods such as ATSBs as was recently done in Mali [43].…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies demonstrate that catching efficiency did increase by 250% when the LED was Pulse Width Modulated (PWM). Furthermore, PWM allows for a reduction of energy consumption by 25% and enables these devices to be solar powered [18]. Although the underlying neurophysiologic mechanisms that trigger this higher attraction are not understood, it can be speculated that modulating pulse width is another interesting parameter to be tuned in these systems.…”
Section: Laser-based Killing Methodsmentioning
confidence: 99%